DIROFILARIOSIS CANINA EN LOS DISTRITOS COLINDANTES CON LA RIBERA DEL RÍO LURÍN - Bravo M., Roxana (2002)
Heartworm is a parasitic disease caused by Dirofilaria immitis. The adult form of the parasite can be found in the right heart and pulmonary arteries, especially in canines. The objective of the study was to quantify the presence of D. immitis in districts located along the Lurín river (Cieneguilla, Pachacamac and Lurín). Blood samples were collected from 177 dogs (males and females) from January till July 2000. The age of the animals varied from 1 to 10 years. Three methods were conducted for diagnosing Dirofilaria: the microhaematocrit and the modified Knott techniques were used for the identification of microfilarias, and ELISA for the determination of secretion / excretion antigens of mature forms. Cieneguilla was the district with the highest frequency of heartworms. 6.4% of positive samples were obtained by the microhaematocrit and modified Knott techniques whereas 12.8% were obtained by ELISA. In Lurín was observed 2.5% using the microhaematocrit and modified Knott techniques whereas 7.5% by ELISA. In Pachacamac was only observed 2% of positive samples by the ELISA technique. In conclusion, the estimated prevalence in the studied area was 7.3% ± 3.8 CI when ELISA was used and 2.8 % ± 2.4 CI when microhaematocrit or the modified Knott techniques were used. The relative low prevalence of the disease in the area does not constitute a serious parasitic problem, however, proper monitoring should be considered.